Simultaneous determination of quinoline and pyridine compounds in gasoline and diesel by differential pulse voltammetry - Okumura, Leonardo L.; Stradiotto, Nelson Ramos [UNESP] (Wiley-Blackwell, 2007)
The presence of trace basic organonitrogen compounds such as quinoline and pyridine in derivative petroleum fuels plays an important role in maintaining the engines of vehicles. However, these substances can contaminate the environment and so must be controlled because most of them are potentially carcinogenic and mutagenic. For these reasons, a reliable and sensitive method was developed for the determination of basic nitrogen compounds in fuel samples such as gasoline and diesel. This method utilizes preconcentration on an ion-exchange resin (Amberlyte IR - 120 H) followed by differential pulse voltammetry (DPV) on a glassy carbon electrode. The electrochemical behavior of quinoline and pyridine as studied by cyclic voltammetry (CV) suggests that their reduction occurs via a reversible electron transfer followed by an irreversible chemical reaction. Very well resolved diffusion-controlled voltammetric peaks were obtained in dimethylformamide (DMF) with tetrabutylammonium tetrafluoroborate (TBAF(4) 0.1 mol L-1) for quinoline (-1.95 V) and pyridine (-2.52 V) vs. Ag vertical bar AgCl vertical bar KClsat reference electrode. The proposed DPV method displayed a good linear response from 0.10 to 300 mg L-1 and a limit of detection (LOD) of 5.05 and 0.25 mu g L-1 for quinoline and pyridine, respectively. Using the method of standard additions, the simultaneous determination of quinoline and pyridine in gasoline samples yielded 25.0 +/- 0.3 and 33.0 +/- 0.7 mg L-1 and in diesel samples yielded 80.3 +/- 0.2 and 131 +/- 0.4 mg L-1, respectively. Spike recoveries were 94.4 +/- 0.3% and 10 +/- 0.5% for quinoline and pyridine, respectively, in the fuel determinations. This proposed method was also compared with UV-vis spectrophotometric measurements. Results obtained for the two methods agreed well based on F and t student's tests.
Keywords: ion-exchange resin; quinoline; pyridine; differential pulse voltammetry; gasoline; diesel